Implementation Of Online Learning During The Covid-19 Pandemic At SD Negeri 0405 Hapung In 2021 - Seri Husni Artati Hsb (STKIP Rokania Pasir Pangaraian, 2022)
One of the learning alternatives as a result of the Covid-19 pandemic in various sectors is education through the application of online learning. This study aims to describe the implementation of eLearning at SD Negeri 0405 Hapung. The research method uses phenomenological qualitative methods. The subjects of this study were teachers and students of SD Negeri 0405 Hapung. Data collection techniques using interviews and documents. Data analysis was carried out through the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the implementation of online learning in Indonesia is running well. The teacher carries out all stages of learning, starting from planning, implementing, and evaluating. Teachers are asked to be more creative in teaching so that students do not get bored quickly